Design and development of semi-indirect non-electric pyrolytic reactor for biochar production from farm waste - PRABHA, B; PUGALENDHI, S; SUBRAMANIAN, P (The Indian Journal of Agricultural Sciences, 2015)
The paper describes the development of semi-indirect non-electric pyrolytic reactor of 1 kg capacity and for optimizing production process of biochar from different farm wastes. Biochar was produced through pyrolysis of farm wastes, viz. maize cob, cotton stalk and coconut shell by using Prosopis julifera as a combustion fuel in the pyrolytic reactor. Biochar production from farm waste was optimized with different mass of combustion fuel such as 0.25, 0.50, 0.75 and 1.0 kg. Maximum residence time for obtaining maximum yield and characteristics of farm waste and biochar were also investigated. The maximum yield of biochar from maize cob, coconut shell and cotton stalks were found to be 34, 33 and 36% respectively. The optimum combustion and pyrolysis mass ratio was found as 0.5:1 for maize cob and cotton stalk and that of coconut shell was 0.75:1. The mass and energy closure efficiency of the developed pyrolysis unit were found to be 85% and 83% respectively. The organic carbon content of biochar ranged as 67-89% for the selected feed-stocks. The results indicated that the maximum amount of biochar was produced with minimum amount of combustion fuel enhancing low-cost by using the reactor. The developed pyrolytic reactor was found economically viable with payback period of 3.2 years. Through characterization of biomass and biochar, it was found that the reduction of bulk density of biochar output (215-278 kg/m3) compared to raw farm waste (450-500 kg/m3) was beneficial to improve soil health of cultivable land.